Phytoremediation of Lead-Contaminated Soil by Using Vetiver Grass (Vetiveria zizanioides L.) - Rawidh Said Abdallah; Arief Rachmansyah; Bagyo Yanuwiadi (Journal of Experimental Life Science)
Lead become a frequent problem in the environment, especially in the soil. However, there are plenty of plant species that can be used to overcome that problem. This study was aimed to analyze the effectiveness of Vetiver grass to reduce hyper-accumulate heavy metal such as lead (Pb) in the soil. Moreover, this study focused on the determination of heavy metals in the soil before plantation and after plantation of Vetiver. The method used was by planting the Vetiver grass in soil that was already treated by lead nitrate, lead chloride, and lead sulfate. Samples were collected from these treated soil every two weeks and samples of the vetiver grass were taken after one week for ten weeks. The result shows that Vetiver grasses are able to remove hyper-accumulate lead from the treated soil.